A risk score to predict the absence of left ventricular reverse remodeling: Implications for the timing of ICD implantation in primary prevention. Issue 5 (May 2018) - Pérez-Rodon, Jordi; Galve, Enrique; Pérez-Bocanegra, Carmen; Soriano-Sánchez, Teresa; Recio-Iglesias, Jesús; Domingo-Baldrich, Eva; Alzola-Guevara, Mila; Ferreira-González, Ignacio; Marsal, Josep Ramon; Ribera-Solé, Aida; Gutierrez García-Moreno, Laura; Cruz-Carlos, Luz María; et al.
Highlights: The achievement of target doses in heart failure (HF) with reduced ejection fraction is feasible in most patients. 50% of patients achieve left ventricular reverse remodeling after HF therapy optimization. 50% of patients lose the potential implantable cardioverter defibrillator (ICD) indication after HF therapy optimization. The proposed risk score may help to decide the timing of ICD implantation. The use of a wearable-ICD may prevent mortality during HF therapy optimization. Abstract: Background: A prophylactic implantable cardioverter defibrillator (ICD) in patients with heart failure and reduced left ventricular ejection fraction (HFrEF) is only indicated when left ventricular ejection fraction (LVEF) reassessment remains ≤35% after 3–6 months on optimal pharmacological therapy. However, LVEF may not improve during this period and the patient may be exposed to an unnecessary risk of sudden cardiac death. This study aimed to determine the incidence and predictors of the absence of left ventricular reverse remodeling (LVRR) after pharmacological treatment optimization in patients with HFrEF to design a risk score of absence of LVRR. Methods: Consecutive outpatients with LVEF ≤35% were included in this observational prospective study. Up-titration of angiotensin-converting enzyme (ACE) inhibitors/angiotensin II receptor blockers (ARBs), beta-blockers, mineralocorticoid receptor antagonists (MRAs), and ivabradine was performed in our Heart Failure (HF) Unit. The absence of LVRR was defined as the persistence of an LVEF ≤35% at the 6-month follow-up. Results: One hundred and twenty patients were included. At the 6-month follow-up, 64%, 76%, 72%, and 7% of patients were at 100% of the target dose of ACE inhibitors/ARBs, beta-blockers, MRAs, and ivabradine, respectively. LVRR was observed in 48% of the patients. Ischemic cardiomyopathy, prolonged HF duration, and larger left ventricular end-diastolic diameter index (LVEDDI) were independent predictors of the absence of LVRR. The risk score based on these predictors showed a c -statistic value of 0.81. Conclusions: Pharmacological treatment optimization is associated with LVRR in approximately half of cases, reducing potential ICD indications in parallel. However, ischemic cardiomyopathy, prolonged HF duration, and larger LVEDDI predict the absence of LVRR and favor ICD implantation without delay. The risk score based on the former predictors may help the clinician with the timing of ICD implantation.